An Integrated Success Model of Internet of Things (IoT)-Based Services in Facilities Management for Public Sector - Sidek N.; Ali N.; Alkawsi G. (MDPI, 2023)
Human resource management; Least squares approximations; Office buildings; Facilities management; Integrated modeling; IS success model; Online questionnaire; Public sector; Public services; Quantitative method; Rapid growth; Success models; Technology readiness; Internet of things; Internet; public sector; questionnaire; technology; Internet; Internet of Things; Public Sector; Surveys and Questionnaires; Technology